Assessment of Oculomotor Function in Patients With Postconcussion Syndrome: A Systematic Review. Issue 5 (September 2017) - Taghdiri, Foad; Varriano, Brenda; Tartaglia, Maria Carmela
Abstract : Background: Concussion and its associated sequel, postconcussion syndrome (PCS), have a debilitating impact on the lives of concussed patients. However, a diagnostic biomarker for this condition is lacking. Recently, there has been a surge of interest in using oculomotor function testing as an objective assessment of patients with PCS. Objectives: To systematically synthesize, appraise, and summarize all published empirical studies that have assessed alteration of oculomotor functions in patients with PCS. Methods: Medline, Embase, PsychINFO, and CINAHL databases searched up to July 2016 for studies that used oculomotor function assessment in patients with postconcussion symptoms. Results: The search identified 1637 citations, and finally 8 case-control studies were included. Of these, 5 studies used a similar task with a target moving in a circular trajectory. Three other studies measured conventional oculomotor tasks such as saccade, vergence, and smooth pursuit eye movements. Conclusions: Currently, there is limited support for the recommendation of oculomotor function assessments for diagnosis and identification of patients with PCS following head trauma. Therefore, more rigorous studies assessing oculomotor function changes in patients with PCS are warranted.